RESPON HEMATOLOGI PASIEN LEUKEMIA MIELOID KRONIK YANG MENDAPAT PENGOBATAN TYROSINE KINASE INHIBITOR SELAMA SETAHUN DI RSUP SANGLAH DENPASAR - I Made Bagus Ambara Putra; Renny A Rena; Ketut Suega (E-Jurnal Medika Udayana, 2015)
HEMATOLOGY RESPONSE CHRONIC MYELOID LEUKEMIA PATIENT WHO GETS TYROSINE KINASE INHIBITOR TREATMENT FOR A YEAR IN GENERAL HOSPITAL CENTER SANGLAH DENPASAR Chronic Myeloid Leukemia (CML) is disorder that cause by reciprocal translocation in chromosome 9 and 22, that produce cimeric oncogene called BCR-ABL, which is the product of protein Tyrosine Kinase and cause uncontrolled proliferation of myeloid cell. The objective of this study is to determine the hematologic response of CML patient who received treatment TKI for a year. This study is Retrospective descriptive study which conduct at Sanglah General Hospital from july to November 2015. A total number of 29 patient were study, all of patient were diagnose as CML. Chronic Myeloid Leukemia patient evaluate to determine the hematologic response after use TKI for a year. Evaluate is done from the beginning diagnose, 3 month, 6 month, 9 month, and 12 month. The information obtaining from medical record and interviews. After evaluate, the mean result of leukocyte prior TKI therapy 227.59 ± 22.03 x 103/mm3 be 14.61 ± 3.45 x 103/mm3 after 12 months receive TKI. The mean hemoglobin prior TKI 9.68 ± 0.42g/dL be 12.07 ± 0.42 g/dL after 12 month receive TKI. The mean thrombocyte  prior TKI 458.32 ± 86.35 x 103/mm3 be 276.79 ± 29.68 x 103/mm3 after 12 month receive TKI. From the result of this study can conclude an improvement of hematologic response CML patient who receive TKI for a year. Decrease in the mean leukocyte, an increase in the mean hemoglobin, and decrease in the mean thrombocyte.